Profil Kondisi Fisik Atlet Bola Tangan Putri Kabupaten Demak Tahun 2022 (Universitas Negeri Semarang, 2022)
This type of research is quantitative descriptive research with tests and measurements. The subjects in this study were demak regency women's handball athletes. The technique used for sampling is purposive sampling. Data collection techniques use test and measurement methods. The background of this research problem is the absence of a special physical trainer for male and female handball athletes in Demak Regency and the low motivation of athletes to do physical exercise. The problem with this study is that the level of physical condition of women's handball athletes in Demak Regency in 2022 is not yet known.The result of this study was that out of 16 athletes aged 17-21 years, there were 2 athletes categorized as very lacking, 1 athlete categorized as less, 7 athletes categorized as moderate, 4 athletes categorized as good, and 2 athletes categorized as excellent.Based on the results of the study, it can be concluded that the physical condition profile of women's handball athletes in Demak Regency is categorized as moderate.